Nicotine Abuse and Neurodegeneration: Novel Pharmacogenetic Targets to Aid Quitting and Reduce the Risk of Dementia - Almahasneh, Fatimah; Gerges, Romany H.; Abu-El-Rub, Ejlal; Khasawneh, Ramada R. (CNS & Neurological Disorders - Drug Targets, 2024)
Nicotine dependence has deleterious neurological impacts. Previous studies found an association between cigarette smoking and accelerating age-related thinning of the brain's cortex and subsequent cognitive decline. Smoking is considered the third most common risk factor for dementia, which prompted the inclusion of smoking cessation in dementia prevention strategies. Traditional pharmacologic options for smoking cessation include nicotine transdermal patches, bupropion and varenicline. However, based on smokers’ genetic makeup, pharmacogenetics can be used to develop novel therapies to replace these traditional approaches. Genetic variability of cytochrome P450 2A6 has a major impact on smokers’ behavior and their response to quitting therapies. Gene polymorphism in nicotinic acetylcholine receptor subunits also has a great influence on the ability to quit smoking. In addition, polymorphism of certain nicotinic acetylcholine receptors was found to affect the risk of dementia and the impact of tobacco smoking on the development of Alzheimer's disease. Nicotine dependence involves the activation of pleasure response through the stimulation of dopamine release. Central dopamine receptors, catechol-o-methyltransferase and the dopamine transporter protein, regulate synaptic dopamine levels. The genes of these molecules are potential targets for novel smoking cessation drugs. Pharmacogenetic studies of smoking cessation also investigated other molecules, such as ANKK1 and dopamine-beta-hydroxylase (DBH). In this perspective article, we aim to highlight the promising role of pharmacogenetics in the development of effective drugs for smoking cessation, which can increase the success rate of smoking quitting plans and ultimately reduce the incidence of neurodegeneration and dementia.
Keywords: dementia